Occupational risks associated with severe COVID-19 disease and SARS-CoV-2 infection - a Swedish national case-control study conducted from October 2020 to December 2021 - Kjell Torén; Maria Albin; Tomas Bergström; Nicola Murgia; Magnus Alderling; Linus Schiöler; Maria Åberg (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVE: This study aimed to investigate whether workplace factors and occupations are associated with SARS-CoV-2 infection or severe COVID-19 in the later waves of the pandemic. METHODS: We studied 552 562 cases with a positive test for SARS-CoV-2 in the Swedish registry of communicable diseases, and 5985 cases with severe COVID-19 based on hospital admissions from October 2020 to December 2021. Four population controls were assigned the index dates of their corresponding cases. We linked job histories to job-exposure matrices to assess the odds for different transmission dimensions and different occupations. We used adjusted conditional logistic analyses to estimate odds ratios (OR) for severe COVID-19 and SARS-CoV-2 with 95% confidence intervals (CI). RESULTS: The highest OR for severe COVID-19 were for: regular contact with infected patients, (OR 1.37, 95% CI 1.23-1.54), close physical proximity (OR 1.47, 95% CI 1.34-1.61), and high exposure to diseases or infections (OR 1.72, 95% CI 1.52-1.96). Mostly working outside had lower OR (OR 0.77, 95% CI 0.57-1.06). The odds for SARS-CoV-2 when mostly working outside were similar (OR 0.83, 95% CI 0.80-0.86). The occupation with the highest OR for severe COVID-19 (compared with low-exposure occupations) was certified specialist physician (OR 2.05, 95% CI 1.31-3.21) among women and bus and tram drivers (OR 2.04, 95% CI 1.49-2.79) among men. CONCLUSIONS: Contact with infected patients, close proximity and crowded workplaces increase the risks for severe COVID-19 and SARS-CoV-2 infection. Outdoor work is associated with decreased odds for SARS-CoV-2 infection and severe COVID-19.